2023
DOI: 10.30935/conmaths/12540
|View full text |Cite
|
Sign up to set email alerts
|

Developing in-service mathematics teachers’ pedagogical content knowledge and skills to teach trigonometry: Using cooperative teaching and learning approach

Abstract: The study is aimed at enhancing pedagogical content knowledge (PCK) and skills of in-service mathematics teachers (IMTs) using cooperative teaching and learning approach (CTLA). A sequential multiple case study was employed to develop eight IMTs knowledge and skills to design, develop, and enact lessons in trigonometry. The lessons were anchored on CTLA in two phases of a professional development arrangement (PDA) initiated in the study. The analysis of classroom observation, interview, CTLA lessons and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Previous studies revealed that students have preconceptions about comprehending mathematical subjects like trigonometry despite the fact that trigonometry is essential knowledge for many important functions, physics and construction (Asomah, Agyei, & Ntow, 2023;Ngu & Phan, 2023). The numerous misunderstandings shown in the learners' responses are frequently a sign of these challenges with high school mathematics (Egodawatte, 2011;Luneta & Makonye, 2010).…”
Section: Trigonometrymentioning
confidence: 99%
“…Previous studies revealed that students have preconceptions about comprehending mathematical subjects like trigonometry despite the fact that trigonometry is essential knowledge for many important functions, physics and construction (Asomah, Agyei, & Ntow, 2023;Ngu & Phan, 2023). The numerous misunderstandings shown in the learners' responses are frequently a sign of these challenges with high school mathematics (Egodawatte, 2011;Luneta & Makonye, 2010).…”
Section: Trigonometrymentioning
confidence: 99%
“…Thus, necessitating various research studies into the features of a productive pedagogy that allows students to make meaning of the subject matter. In fact, previous research undertaken by us indicates that teachers' inability to relate to features of a meaningful-based teaching approach have an effect on students in the tertiary institutions [1] and at the SHS in particular [2][3][4]. There seems to be no unanimity of purpose on a single approach to teaching mathematics [5].…”
Section: Introductionmentioning
confidence: 98%
“…In particular, the inability on the part of students to establish the relationships that exist in the three main trigonometric concepts of sine, cosine, and tangent of an angle [13,14]. The import of this act is mirrored in the abysmal performance of students in trigonometry as highlighted in various examination reports of second cycle institutions [2]. Additionally, the teaching and learning of trigonometrical concepts require an understanding of multiple interrelated mathematical concepts, such as algebraic transformation skills, geometry knowledge, and reasoning of graphical representation of concepts [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of individual and group accountability is aimed at enabling learners within a group to independently and collectively grasp those specifically that are related to the subject matter. On the other hand, promotive face-to-face interaction focuses on creating activities that encourage students to be active in their own learning during face-to-face interaction [8].…”
Section: Introductionmentioning
confidence: 99%